High‐Throughput Optical Mapping of Replicating DNA. Issue 9 (6th August 2018) - De Carli, Francesco; Menezes, Nikita; Berrabah, Wahiba; Barbe, Valérie; Genovesio, Auguste; Hyrien, Olivier
Abstract: DNA replication is a crucial process for the universal ability of living organisms to reproduce. Genome‐wide methods to map DNA replication use large cell populations, which smoothes out variability between chromosomal copies. Single‐molecule methods may reveal this variability but remain refractory to automation, precluding genome‐wide analyses. Here, the Bionano Genomics Irys system, an optical DNA mapping device, is repurposed for high‐throughput optical mapping of replicating DNA (HOMARD). HOMARD combines direct fluorescent labeling of replication tracks and nicking endonuclease sites with DNA linearization in nanochannel arrays and dedicated image processing. The robustness of this approach is demonstrated by an ultrahigh coverage (23 311×) replication map of bacteriophage λ‐DNA in Xenopus egg extracts. This coverage, by far the highest ever reported for a single‐molecule replication study, confirms with unprecedented statistical significance the lack of sequence preference for replication initiation in this system. The tools developed here open the way to genome‐wide analysis of DNA replication at the single‐molecule level and may be readily adapted for similar studies of other epigenetic features. Abstract : Here, a commercial optical DNA mapping device is repurposed for high‐throughput optical mapping of replicating DNA (HOMARD). HOMARD combines direct fluorescent labeling of replication tracks and nicking endonuclease sites with DNA linearization in nanochannel arrays and dedicated image processing. The methodology provides by far the highest coverage single molecule replication map ever reported for a eukaryotic chromatin template.